AN ANALYSIS DIGITALTEXTBOOK FOR 2ND GRADE STUDENTS “MY NEXT WORDS” - Indah Yusmulya Putri; Evi Karlina Ambarwati (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
This study aims to analyze books with quality assessment and content analysis, this study describes the use of digital textbooks in managed learning for Grade 2 Elementary School students, this type of research method is used to discuss the use of textbooks used forincrease student learning motivation at the elementary school level. The book analyzed is a book published by the author EYLC team with the book title "Student’s Book for Elementary School – My Next Words Grade 2. The use of textbooks for students is highly recommended to be used as a means of learning for students, many advantages that can be used to be applied in everyday life, repetition of the material can also be used to train students '' learning skills in learning at school and at home, its practical use makes it easier for students to learn it